Analisa Kinerja Cyclone Combustor Pada Proses Downdraft Gasifier Dengan Media Sekam Padi Untuk Kapasitas 10 Kg/Jam - A Wahyu Cahyo Purnomo; F X Eko Arianto (Politeknik Manufaktur Negeri Bangka Belitung, 2016)
Biomass potency in Indonesia is very abundant both from the animal manure or plant. Agriculture and plantations waste which are abundant can be utilized as the energy source. One of them is the rice husk. This experiment used rice husk gasification method with downdraft gasifier to turn it into a combustible gas that will be burned in the combustion chamber cyclone. The advantage of gasification compared to the method of the direct combustion is cleaner burning and particulates and contaminants can be removed before burning. The cyclone fuels can produce good mixing which is suitable for gas with low calorific value. The composition of syngas produced by gasification of rice husk are H2 13,6%, CO 14,9%, CO2 12,9% dan CH4 2,3% [1]. After leaving the reactor syngas entry cyclone separator to remove moisture and contaminants, and then go to the storage tank and eventually went to cyclone fuel to be burned after mixing with air through a different inlet. After that the different value of AFR will vary to see the changes in temperature of the flame, the fire position in the combustion chamber and the flame shape. From the experimental results in AFR = 1.59 fire in the combustion chamber air beetween 1 and 2, in the AFR = 1.14 The fire in the combustion chamber in the plane 2, in AFR = 0.69 fire in the combustion chamber 3 and in the air beetween AFR = 0.27 fire outside the combustion chamber after mixing withfresh air.